(3GdeWhd Ydi JdNjU GdeaJGMs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3hGdeJYOO GdYbdj cMOI GdfXQ hceGd GdMPQ hENaGA GdSaGOs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3eRGhdI GdeWGjG HGdNWi bO CKQJ ajgG hfbUJ ef bhGgG abhdg hNWi GdegQjI YWa Ydi SQi dG Ydi bhdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 219s
(3eYLe GdeDdajf(B: 3 / 849s
(3cTa GdXfhf(B: 1 / 474s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdHdGZIs